CHALLENGES AND PERSPECTIVES OF LAW AND DIGITALIZATION: CASE STUDY OF CONTRACT LAW - Armand Krasniqi; Mersiha Kalac Kacamakovic (Human Research in Rehabilitation, 2023)
The paper focuses on highlighting the weaknesses and lack of legislation for the electronic notarization of electronic contracts, not only in Kosovo’s business field. The idea of electronic notarization is new in Kosovo and is considered a complex task for the regulation of contractual obligations, which condition the modern activities of e-business. The dynamics and dimensions of e-business development strongly influence the change in the techniques of concluding formal contracts at a distance through information technologies. New legislative practices in the modern world are successfully managing to eliminate or reduce these obstacles, which unintentionally complicate and slow down contractual legal relations between business partners. Notary services are no exception to this trend. Despite the positive trend, the legislation in Kosovo seems to be only in its beginnings, and as such it does not enable and guarantee business partners the electronic notarization of contracts, but unfortunately, there is no debate and no concrete initiatives so far. The first phase, which would better regulate this field, concerns the standardization through the validation of these contracts in the territory of Kosovo through criteria that prove and guarantee the accuracy of the contract.